Rising surface ozone in China from 2013 to 2017: A response to the recent atmospheric warming or pollutant controls?. (1st February 2021) - Li, Mengmeng; Wang, Tijian; Shu, Lei; Qu, Yawei; Xie, Min; Liu, Jane; Wu, Hao; Kalsoom, Ume
Abstract: With the enactment of Air Pollution Action Plan in 2013, the air quality improved in most Chinese cities, except that surface ozone (O3 ) increased markedly. Some recent studies have examined this issue and presented controversial opinions, but only focus on summertime ozone increase. This study extends a comprehensive analysis of the influencing factors on China's ozone changes from 2013 to 2017 out of the summer season, combining satellite data, ground measurements and model analyses. The annual trends of air pollutants, e.g., increase in 95th percentile O3 concentration (+1.4–8.7 μg m −3  yr −1 ), and decreases in fine particulate matter (PM2.5 ; −4.0~−7.5 μg m −3  yr −1 ) and sulfur dioxide (−2.6~−9.7 μg m −3  yr −1 ) are uncovered by satellite and observational data. Model results show that the attributions of surface O3 changes from 2013 to 2017 vary spatially and seasonally, and most regions are more affected by emission changes (−9.5–47.0 μg m −3 ) rather than meteorological changes (−8.1–21.3 μg m −3 ). In specific regions and seasons, e.g., south/southwestern and eastern China south of 35°N in May and July, the surface O3 responses to climate variability could have an equal or even greater importance than emission changes. In these major pollution control regions, e.g. northern and mid-eastern China, the precursor emissions control (11–35%) contributes in the same degree as the changes in aerosol effects (35–38%) to surface ozone enhancement in the warm seasons. More scientific emission controls and climate adaptation strategies are required to attain the synergetic control of atmospheric particulate matter and ozone in China. Graphical abstract: Image 1 Highlights: Air pollution trends are uncovered by satellite data and observations. The attributions of surface O3 changes are more affected by emission changes. O3 response to atmospheric warming is dominant south of 30°N in warm season. NOx and VOCs control contributed equally as aerosol effect in NCP and East China.